Antiproliferative activity of bicyclic benzimidazole nucleosides: synthesis, DNA-binding and cell cycle analysis. Issue 17 (13th April 2016) - Sontakke, Vyankat A.; Lawande, Pravin P.; Kate, Anup N.; Khan, Ayesha; Joshi, Rakesh; Kumbhar, Anupa A.; Shinde, Vaishali S.
Abstract : Bicyclic benzimidazole nucleosides were synthesized fromd -glucose as a starting material. DNA binding, antiproliferative activity and cell cycle analysis were performed. Abstract : An efficient route was developed for synthesis of bicyclic benzimidazole nucleosides1–4 from readily availabled -glucose. The key reactions were Vörbruggen glycosylation and ring closing metathesis (RCM). Primarily, to understand the mode of DNA binding, we performed a molecular docking study and the binding was found to be in the minor groove region. Based on the proposed binding model, UV-visible and fluorescence spectroscopic techniques using calf thymus DNA (CT-DNA) demonstrated a non-intercalative mode of binding. Antiproliferative activity of nucleosides1–4 was tested against MCF-7 and MDA-MB-231 breast cancer cell lines and found to be active at low micromolar concentrations. Compounds2 and4 displayed significant antiproliferative activity as compared to1 and3 with the reference anticancer drug, doxorubicin. Cell cycle analysis showed that nucleoside4 induced cell cycle arrest at the S-phase. Confocal microscopy has been performed to validate the induction of cellular apoptosis. Based on these findings, such modified bicyclic benzimidazole nucleosides will make a significant contribution to the development of anticancer drugs.